2009
DOI: 10.1590/s1413-70542009000700010
|View full text |Cite
|
Sign up to set email alerts
|

Características visuais da embalagem de café no processo de decisão de compra pelo consumidor

Abstract: Conduziu-se este trabalho, com o objetivo de investigar, usando grupos de foco, atitudes, opiniões, conceitos e pensamentos de consumidores sobre embalagens de café torrado e moído que refletem na sua decisão de compra. Três sessões de grupo de foco de 90 minutos foram realizadas (duas em Viçosa/MG e uma em Londrina/PR), num total de 24 participantes. Foram apresentadas cinco embalagens de café (sendo quatro orgânicas, em razão da maior preocupação em obter dados sobre café orgânico) para estimular a conversaç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
1
2
0
1
Order By: Relevance
“…Regarding the effect of the packaging colour on consumer emotions, approximately 17.83% of volunteers answered that the red colour used in coffee packaging brings a positive attitude or feeling, such as agitation, attraction, alertness and hunger (Table 2). This result corroborates with that previously observed by Lucia et al, 23 who concluded that almost 75% of respondents in that study preferred the red colour in coffee packaging. The red colour is associated with signalling, so they draw more attention and stimulate the nervous system to sympathize with this colour 24 .…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Regarding the effect of the packaging colour on consumer emotions, approximately 17.83% of volunteers answered that the red colour used in coffee packaging brings a positive attitude or feeling, such as agitation, attraction, alertness and hunger (Table 2). This result corroborates with that previously observed by Lucia et al, 23 who concluded that almost 75% of respondents in that study preferred the red colour in coffee packaging. The red colour is associated with signalling, so they draw more attention and stimulate the nervous system to sympathize with this colour 24 .…”
Section: Resultssupporting
confidence: 93%
“…Concerning the green colour (Table 2), it was possible to verify that the volunteers associated this colour in coffee packaging with artisanal, special, organic, vegan and ecological products. According to Lucia et al, 23 the packaging with the most significant impact on consumers looking for organic products is green. The second dimension that received the most response was that associated with positive attitudes and feelings.…”
Section: Resultsmentioning
confidence: 99%
“…Della Lucia et al (2009) point out that most of the consumers evaluated in the survey (a total of 75%) reported preferring brown and reddish colors for coffee packaging, claiming that "the color for coffee is brown with red". The possibility was raised by some consumers (37.5%) that green was associated with the organic product, since all the labels on the organic coffee packages had this color, at least in some details.…”
Section: Exploring the Field Of Agricultural And Biological Sciencesmentioning
confidence: 99%
“…Em relação à produção de café orgânico, observa-se que esta tem aumentado a cada ano no Brasil, sendo um reflexo da demanda mundial por alimentos orgânicos, considerados de qualidade e saudáveis (LUCIA et al, 2009). O conjunto dos processos de produção da agricultura orgânica é baseado na fertilidade do solo, como função direta do seu conteúdo de matéria orgânica (ORMOND et al, 2002).…”
Section: Introductionunclassified